2017
DOI: 10.1111/jcmm.13144
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of let‐7f activates TGF‐β/ALK5 pathway and leads to impaired ischaemia‐induced neovascularization after cigarette smoke exposure

Abstract: This study sought to determine the potential role of microRNAs (miRNAs) in the detrimental effects of cigarette smoke on angiogenesis and neovascularization. Using large‐scale miRNA profiling and qRT‐PCR analyses, we identified let‐7f as a pro‐angiogenic miRNA which expression is significantly reduced in HUVECs treated with cigarette smoke extracts (CSE), and in the ischemic muscles of mice that are exposed to cigarette smoke (MES). In a mouse model of hindlimb ischaemia, intramuscular injection of let‐7f mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
0
27
1
Order By: Relevance
“…A recent study from Dhahri et al . observed the reduced expression of let-7f in HUVECs treated with cigarette smoke extracts (CSE) and in the ischemic muscles of mice exposing to cigarette smoke, and they found that forced expression of let-7f promoted angiogenesis in HUVECs exposed to CSE by targeting TGF-βRI 31 . In this study, we also found the down-regulation of let-7f in the MI mice, which contains two potential binding sites for PFL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Dhahri et al . observed the reduced expression of let-7f in HUVECs treated with cigarette smoke extracts (CSE) and in the ischemic muscles of mice exposing to cigarette smoke, and they found that forced expression of let-7f promoted angiogenesis in HUVECs exposed to CSE by targeting TGF-βRI 31 . In this study, we also found the down-regulation of let-7f in the MI mice, which contains two potential binding sites for PFL.…”
Section: Discussionmentioning
confidence: 99%
“…12 months after anti-diabetic therapy, let-7f was normalized 48 . Not only high plasma glucose levels, but also immune activation by LPS or cigarette smoke provokes let-7f decreases 49 , 50 . The decrease in let-7f levels under cigarette smoke provoked anti-angiogenic effects via modulation TGFbeta-pathway in endothelial cells 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Not only high plasma glucose levels, but also immune activation by LPS or cigarette smoke provokes let-7f decreases 49 , 50 . The decrease in let-7f levels under cigarette smoke provoked anti-angiogenic effects via modulation TGFbeta-pathway in endothelial cells 50 . Thus, the cellular source of the identified reductions in miRNA levels in atherosclerotic plaques may, primarily, come from ECs and VSMCs, and contribute to atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…In our study two let‐7f miRNAs were regulated contrary after preconditioning with isoflurane, let‐7f‐2 was up‐regulated whereas let‐7f‐1‐3p was down‐regulated. Let‐7f is generally associated with myocardial infarction and angiogenesis [68,69]. The precise mechanisms and targets of our let‐7f miRNAs and their potential cardioprotective effects need to be unravelled in future studies [70–72].…”
Section: Discussionmentioning
confidence: 99%